CHANGES IN MUSCLE STRENGTH MOMENTS AND WEIGHTLIFTING PERFORMANCE GAINS DURING TWO-YEAR TRAINING CYCLE OF YOUNG WEIGHTLIFTERS - Szyszka, Paulina (Theory and Practice of Physical Culture, 2022)
Objective of the study of the research was to evaluate changes in muscle strength moments as well as to compare these changes with the performance gains in weightlifting results during a 2-year training cycle of young weightlifters. Methods and structure of the study. The study was conducted in a group of 20 athletes training weightlifting with at least one year of training experience and 2nd sport class. Peak torque values of the muscles of the upper and lower limbs and the trunk were measured under isometric conditions. The measurements were carried out on properly prepared LR2-P test stands (JBA Zb. Staniak, Poland). Results and conclusions. The results achieved in individual weightlifting exercises were recalculated according to Sinclair’s scores in order to eliminate the influence of the competitors’ body mass change on the achieved results. Among the studied group of athletes, statistically significant (p<0.05) gains in the value of moments of the analysed muscle groups were confirmed. The greatest gains among the analysed muscle groups occurred in the case of trunk extensors. The literature provides evidence that strength training of the trunk extensors in sport is important in the prevention of low back pain (LBP). Furthermore, it translates into the high performance in many sports. Therefore, these muscle unit strength gain confirmed in this study may translate into a lack of pain and the ability to continue specialised training for two years among young athletes. Gains in trunk extensors correlate significantly with gains in snatch performance, which may directly translate into performance in weightlifting, as this is an exercise performed during competitions.